Using self-tapping screw to reinforce dowel-type connection in a timber portal frame. (1st January 2019) - Zhang, Cong; Guo, Haibo; Jung, Kiho; Harris, Richard; Chang, Wen-Shao
Highlights: Full-scale testing on timber portal frame with screw reinforcement. Innovative use of self-tapping screws. Qualitative discussion on the effectiveness of screw reinforcement. Abstract: In this study, partially threaded self-tapping screws have been used as reinforcement on timber portal frames to enhance mechanical performance of dowel-type connections. Experimental tests on unreinforced and reinforced portal frames showed that reinforced frames achieved a 31% and 51% increase in moment-resisting capacity and ultimate rotation, respectively. The test on the reinforced frames was stopped when the stroke on the hydraulic jacks had been reached, while 20% of load drop was not observed. The test results demonstrated the performance of partially threaded self-tapping screws which reduces the drive-in torque when compared to fully threaded self-tapping screws. A theoretical prediction on the characteristic moment-resisting capacity of screw reinforced portal frames is proposed.